(untitled) (Research, Society and Development, 2021)
The allelopathic activity of oils acts directly in seedling germination and growth processes, affecting the initial development, since the constitution and the class to which these oils belong are directly related to the harmful effects to the seeds. The present work aimed to analyze the allelopathic effect of copaíba oil on seed germination and initial development of tomato seedlings. The seeds of two lots were placed to germinate in a substrate moistened with 0; 0.01; 0.05; 0.10; 0.15 and 0.20% copaíba oil. 200 tomato seeds were used per treatment, distributed in four replications. Germination, germination speed index and seedling length were evaluated. The germination percentage and the germination speed index of the seeds of the two batches did not differ from each other, however seeds from batch 1 responded positively to the application of copaíba oil. Regarding the length of seedlings, the concentration of 0.01% was higher than the others. With regard to lot 2, the absence of copaíba oil provided a longer seedling length. The concentrations of copaíba oil did not reduce the percentage of germination, germination speed index in a positive way. For the observation of the allelopathic effect of copaíba oil on tomato seeds, it is recommended to use concentrations higher than those used in the present study.